Sacramentalism in the Poetry of Philip Larkin - King, Don W. (Christian scholar's review, 2009)
Although undoubtedly there is a strong current of skepticism running through the poetry of Philip Larkin, Don W. King argues that Larkin’s use of sacramental motifs suggests a pattern illustrating an ever-present—though often muted—fascination with transcendent meaning. That is, despite Larkin’s agnosticism, his frequent focus on sacramental motifs belies the idea that he dismisses completely the possibility of there being transcendent meaning. The focus of this essay is upon the sacramental in his poetry—what it is for Larkin, its regular appearance in poems that may be better called meditations and its role in what Seamus Heaney calls the “visionary moment.” Mr. King is Professor of English at Montreat College.